Hubungan Antara Kontrol Diri dengan Impulsive Buying Produk Fashion di Masa Pandemi Pada Mahasiswa Melalui Aplikasi Belanja Online - Desriyani Chindhy Salamba; Krismi Diah Ambarwati (Economics and Digital Business Review, 2023)
This research was conducted to determine the relationship between self control and impulsive buying of fashion products during the pandemic in students through online shopping applications for students throughout Indonesia. Students are individuals who are in the transition period from adolescence to adulthood and will make efforts to explore themselves such as trying various kinds of fashion products. The research method used is quantitative with correlational analysis, with a total of 350 participants who are students of the class 2018-2022 throughout Indonesia. Data collection was carried out using a self control scale with an alpha cronbach value of 0.750 and an impulsive buying scale with an alpha cronbach value of 0.838. Based on the product moment correlation test, pearson is known to have a value of r (r= -0,415) with a value of sig = 0.000 (p < 0.05) then it means that there is a significant negative relationship between self control and impulsive buying. The higher the self-control, the lower the impulsive buying in students when shopping for fashion products. This research is useful for students to be able to control themselves from their needs, not the desire to buy fashion products online.